RELIGIÃO E FRONTEIRA: EM DIÁLOGO COM PAUL TILLICH NO BRASIL - Rodrigues, Felipe Fanuel Xavier (2009)
Our objective in this research is to inquire into studies that dialogue with Paul Tillich in Brazil in the last years, seeking to map their tendency, departing from religion. In order to do this, it was necessary to verify the scientific production done in Paul Tillich Association of Brazil, through Correlatio journal, considering the theoretical referential on religion and boundary. We have used these themes, religion and boundary, the meanings of which were taken from Tillich s own theory, as the main categories of analysis in our work. We have indicated the contribution that Brazilian researchers who are interested in Tillich s ideas have presented to Religious Studies. Besides, we have observed specially that Tillich s thought is in a boundary situation in Brazil between what he has said and the way he is interpreted in this country, where religion in a narrow sense concerns scholars much more than religion in a broad sense. This dissertation is structured in three moments: number one, showing how the boundary can be seen as a hermeneutical place for religion; number two, presenting some openings with which Tillich deals with religion subject, number three, analyzing studies in dialogue with Tillich in Brazil, through the categories religion and boundary.(AU)